Answer:
![\cos(\alpha +\beta)=(2)/(3)(1-(√(5))/(5))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/prtozuay5hmy16zd2gv8piiz4d7d18mcfi.png)
Explanation:
Let the hypotenuse of the smaller triangle be h units.
Then; from the Pythagoras Theorem.
![h^2=4^2+2^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tyrel3fhmsvf6ljzd99wzs24xn1aubwov8.png)
![h^2=16+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m45txfkx8u7wmuy6qpx2cnx8hgc2gsyjjj.png)
![h^2=20](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7qlbrx4klyts7a091u25ojfbrjhgjz7402.png)
![h=√(20)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/znhrw8mlrrwynk12p2nm1uezadhk23yo8n.png)
![h=2√(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sv8m4u3pddjlv7do5wrd4rabyaci2arzr7.png)
From the smaller triangle;
and
![\sin(\alpha)=(2)/(2√(5) )=(1)/(√(5) )](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vfdxoa2kkxkkayy8m1goeq49zhtkz84g3w.png)
From the second triangle, let the other other shorter leg of the second triangle be s units.
Then;
![s^2+4^2=6^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nj11pgz5s52uqsgbf3q8ut4u25q1pig8zu.png)
![s^2+16=36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/42xzegfvg59vfkaaf8og1s2q25ur2gz98d.png)
![s^2=36-16](https://img.qammunity.org/2020/formulas/mathematics/middle-school/67gy5w0ibdl0fkmhnc6f11bpo1ivf5xxmy.png)
![s^2=20](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vd2v643lryd5wqlk6nk5ydoh9y130p91n7.png)
![s=√(20)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t1njr5ahk07m5zp1xw88jp5dimmirusjp5.png)
![s=2√(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6t4w8wkduqkarqrm6rbis1njt7pvhbcm4i.png)
![\cos(\beta)=(2√(5) )/(6)=(√(5) )/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v78fuxml4z0uaauy83gx9jzjba53zglhbk.png)
and
![\sin(\beta)=(4)/(6)=(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/khyhmqkhez0c89sw2f3hq0m353c7r8rxap.png)
We now use the double angle property;
![\cos(\alpha +\beta)=\cos(\alpha)\cos(\beta) -\sin(\alpha)\sin(\beta)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/godmoxhivwziss2zw0z2f36bownjwkwxw8.png)
we plug in the values to obtain;
![\cos(\alpha +\beta)=(2)/(√(5) )* (√(5) )/(3)-(1)/(√(5) )* (2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rmucxjwnx5cynamw5j01ygrd4rp1p7vv56.png)
![\cos(\alpha +\beta)=(2)/(3)(1-(√(5))/(5))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/prtozuay5hmy16zd2gv8piiz4d7d18mcfi.png)